FSH/LH co-stimulation in Advanced Maternal Age (AMA) and hypo-responder patients – Arabian gulf delphi consensus group - Awwad, Johnny; Peramo, Braulio; Elgeyoushi, Bohaira; Melado, Laura; Salame, Anastasia; Chawla, Monika; Jibrel, Salam; Detho, Sajida; Al Rumaih, Hazem; Tomsu, Mustapha; Fahim, Khaled; Abd-ElGawad, Mohamed; et al. (Frontiers in Endocrinology, 2024)
Background: In a global effort to assess expert perspectives on the use of recombinant human luteinizing hormone (r-hLH) and recombinant human follicle-stimulating hormone (r-hFSH), a consensus meeting was held in Dubai. The key aim was to address three critical questions: What factors influence follicle response? Which patients benefit from LH supplementation? What are the optimal management strategies? Methods: A panel of thirty-six experts reviewed the initial statements and references proposed by the Scientific Coordinator. Consensus was defined as agreement or disagreement by more than two-thirds (66%) of the panel members for each statement. Results: Thirty-five statements were formulated, of which thirty-one reached consensus. For patients with Hypo-Response to Gonadotropin Stimulation (20 statements), all identified risk factors, including advanced age, high BMI, and chronic conditions, achieved unanimous agreement. Diagnostic approaches, such as the inclusion of POSEIDON criteria and hormone levels, were endorsed by the majority, with over 90% agreement. Management strategies, particularly individualized stimulation protocols and optimized scheduling, garnered broad consensus, with only one statement falling short of the threshold. Additionally, in cases of severe FSH and LH deficiency, combining r-hFSH with r-hLH was found to improve pregnancy rates and cost efficiency compared to human menopausal gonadotropin (hMG). For patients with Advanced Maternal Age (AMA) (15 statements), there was strong agreement on the use of oral contraceptive pills and estrogen priming. Recommendations concerning antagonist protocols and dosing of r-hLH and r-hFSH also achieved high levels of consensus. Significant agreement supported r-hLH supplementation and a tailored approach to luteal phase support. However, there were mixed opinions on the route of progesterone administration, with some experts expressing neutral or disagreeing views. Despite these differences, unanimous consensus was reached on markers of treatment success, particularly live birth rates, pregnancy rates, and embryo development, underscoring the importance of these outcomes in evaluating treatment efficacy. This consensus provides a practical clinical perspective to a wide range of global professionals on the strategies employed during key phases of Assisted Reproductive Technology (ART) treatment. To further improve outcomes, incorporating additional clinical insights on ART approaches, alongside existing guidelines and policies, may offer valuable guidance for optimizing patient care.